Mahmoud Darwish, Why Did You Leave the Horse Alone? - Boullata, Issa J. (Hagar: Studies in Society and Culture, 2008)
For the Arabic language in Mahmoud Darwish’s hand is indeed a magic wand with which he transforms words into new images and novel ideas that become co-citizens of his virtual homeland of the free. Mahmoud Darwish here confirms that he accepts to live with the Arabic language, but only if it remains vibrant and vivid and ever-alive with notions of freedom and serves the continuing basic and indispensable requirements of life, only if it remains a bread with "the salt of freedom."